2009
DOI: 10.1053/j.seminhematol.2008.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Stem Cells and Human Acute Lymphoblastic Leukemia

Abstract: Leukemias and other cancers have been proposed to contain a subpopulation of cells that display characteristics of stem cells, and which maintain tumor growth. That most anti-cancer therapy is directed against the bulk of the tumor, and possibly spares the cancer stem cells, may lie at the heart of treatment failures with conventional modalities. Leukemia stem cells are fairly well described for acute myeloid leukemia (AML), but their existence and relevance for acute lymphoblastic leukemia (ALL) is less clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 42 publications
(51 reference statements)
0
30
1
Order By: Relevance
“…20 We found that the expression levels of tmTNF-a were much higher in HSC-enriched leukemia fractions than in nonmalignant cells (P , .001; Figure 1E). However, no significant differences in the levels of tmTNF-a expression could be observed among various subtypes of AL ( Figure 1F-G).…”
Section: Cd7mentioning
confidence: 84%
“…20 We found that the expression levels of tmTNF-a were much higher in HSC-enriched leukemia fractions than in nonmalignant cells (P , .001; Figure 1E). However, no significant differences in the levels of tmTNF-a expression could be observed among various subtypes of AL ( Figure 1F-G).…”
Section: Cd7mentioning
confidence: 84%
“…CD34 + cells are ideally suited for this analysis, since many translocation events in leukemias and lymphomas are thought to occur within the hematopoietic stem cell population or in early progenitors derived from this population (Bonnet and Dick 1997;Bernt and Armstrong 2009). A set of 74 translocation genes, defined as translocated in at least 10 clinical cases of hematologic malignancies, was selected using the Mitelman Database of Chromosome Aberrations (translocation genes) (Supplemental Table S1).…”
Section: Computational Analysis Of Chromatin Features At Recurrent Brmentioning
confidence: 99%
“…22,23 A single clonal population gives rise to the lymphocyte pool, thus the concept of polyclonality versus monoclonality is routinely applied in the diagnostic assessment of lymphoid neoplasm. 24 To assess whether the lymphoid graft derived from AML patients observed in NOD/SCID IL2R␥c null mice was monoclonal or polyclonal in origin, clonal rearrangements of TCR genes, which reflect clonal expansion of T-lymphocytes, were measured in engrafted samples by PCR.…”
Section: Nsg-engrafting Amls Produce a Monoclonal T-cell Lymphoprolifmentioning
confidence: 99%